IRRI Seed Health and Logistics Unit Awareness Week highlights its critical role in the safe distribution of germplasm for R&D - IRRI Seed Health and Logistics Unit (International Rice Research Institute, 2023)
The IRRI Seed Health and Logistics Unit (SHU) showcased its activities and available services involving the exchange of seed and non-seed biomaterials during its 2023 Awareness Week on November 24-30, 2023.